Do tax subsidies for retirement saving impact total private saving? New evidence on middle-income workers - Camilla Skovbo Christensen; Bastian Emil Ellegaard (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2022)
We exploit exogenous variation from a pension reform in Denmark to estimate the effect of tax subsidies on total private saving. We present new evidence on individuals in the middle of the income distribution and show that a reduction in tax subsidies for retirement saving reduces total private saving. The reform changed the tax incentives for saving in the pension scheme that holds the highest tax advantage for middle-income workers in Denmark. We find that for each unit of reduced saving in this pension scheme, only 63 percent is substituted to other types of saving.
Keywords: H24; H31; D14; G51; 330; Crowd-out; Savings; Retirement; Tax incentives; Household finance